2019
DOI: 10.3390/jcm8091391
|View full text |Cite
|
Sign up to set email alerts
|

Smoking as an Independent Risk Factor for Hepatocellular Carcinoma Due to the α7-Nachr Modulating the JAK2/STAT3 Signaling Axis

Abstract: Background: Hepatocellular carcinoma (HCC) is a worldwide health problem. Currently, there is no effective clinical therapeutic strategy for HCC. Smoking is associated with several malignant diseases including cancers. Experimental approach: However, the impact of smoking on HCC is still unresolved. Retrospectively reviewed HCC patients diagnosed between 1 January 2010 and 31 December 2015 at Taipei Medical University-Shuang Ho Hospital (Ministry of Health and Welfare). We found that smoking was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In the current study, we found that smoking was associated with a recurrence risk of 2 to 3 and 3 to 5 years after HCC. The underlying mechanism might be that nicotine increases the expression of α-7-nicotinic acetylcholine receptor (α-7-nAChR), leading to recurrence through the JAK2/STAT3 signaling pathway ( 46 ). A previous study found that the history and amount of smoking were both risk factors for the progressive recurrence of HBV-related HCC ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we found that smoking was associated with a recurrence risk of 2 to 3 and 3 to 5 years after HCC. The underlying mechanism might be that nicotine increases the expression of α-7-nicotinic acetylcholine receptor (α-7-nAChR), leading to recurrence through the JAK2/STAT3 signaling pathway ( 46 ). A previous study found that the history and amount of smoking were both risk factors for the progressive recurrence of HBV-related HCC ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…BAX and cleaved caspase 3 are widely reported apoptotic factors [ 30 ], and JAK2/STAT3 are potent pathway mediating inflammatory responses in the SAP-induced hepatocellular injury model [ 31 ]. For apoptotic factors, after the establishment of the SAP-induced hepatocellular injury model, relative mRNA levels of BAX increased at 6 hours, 12 hours, and 24 hours ( Figure 5(a) , P < 0.05) when compared with those in the SG group.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study highlighted smoking as an independent risk factor for HCC progression through α 7nAChR and JAK2 signaling. [ 16 ]. In this study, we investigated the mechanisms underlying nicotine's effects on HCC progression through α 7nAChR and JAK2 signaling and the reversal of those effects by DHCT, a novel kinase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study by our group, we demonstrated by applying the HCC patient's clinical samples that smoking is an independent risk factor for HCC progression through the α 7nAChR and JAK2 signalling [ 16 ]. In the cholinergic system, α 7nAChRs facilitates many different pathways, it is extensively studied in association with the anti-inflammatory pathways [ 17 ].…”
Section: Introductionmentioning
confidence: 99%